(untitled) (Journal of Informatics and Mathematical Sciences, 2013)
We introduce the concept of the Green-Kehayopulu relations in le-ternary semigroups mimics the definition of the Green-Kehayopulu relations in le-semigroups that was introduced in 2002 by Petro and Pasku [3] and investigate the Green-Kehayopulu relations in le-ternary semigroups.